PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. TOM BURGER GROUP KABUPATEN LIMA PULUH KOTA - Cika Anjeli Cika; Defidelwina; Laily Fitriana (SUNGKAI, 2026)
This research is based on the problem of employee motivation at PT Tom Burger Group which is proven by the existence of problems in implementing new ideas, time management, and team coordination in performance. This study aims to analyze the level of work motivation, employee performance, and the influence of work motivation on performance in Lima Puluh Kota Regency. This research method is quantitative. The number of samples is 41 employees, and data is collected through surveys, questionnaires, and documentation. The analysis technique uses interval scale analysis and simple regression. The results of the study showed that employee work motivation is classified as high with a score of 1,934 (average 2.95), while employee performance is in the moderate category with a score of 1,694 (average 2.58). Regression analysis shows that work motivation has a significant effect on employee performance with an RÂ² value of 0.703, which means that 70.3% of the variation in performance can be explained by work motivation, while 29.7% is influenced by other factors outside this study.